Nano α-FeOOH Modified Carbon Paste Electrode for Arsenic Determination in Natural Waters - Rui Lin Zhang; Shijun HONG; Dongxian ZHANG; Shengjian LI; Zixi ZHAO; Huiping BAI (Medžiagotyra, 2018)
A novel method for determination of inorganic arsenic in natural water, based on nano ferric hydroxides (FeOOH) preconcentration and electrochemistry detection has been developed. As the nano α-FeOOH could successfully act as the adsorbent and electrode matrix modifier, the method presents great potential in practical routine analysis of inorganic arsenic. With optimization of the experimental conditions, nano α-FeOOH modified carbon paste electrode (α-FeOOH@CPE) was obtained by mixing 0.03 g of nano α-FeOOH and 0.02 g graphite powder in n-eicosane as an adhesive and then embedding them in a Teflon tube. Cyclic voltammetry, chronoamperometry and high resolution transmission electron microscopy were used to check and confirm the presence of nano α-FeOOH on the carbon paste electrodes. According to the results, α-FeOOH@CPE showed a considerably higher response to As(III) in comparison with the bare CPE, indicating the α-FeOOH has well selective enrichment for As(III). The developed modified electrode showed a linear range of 1.0 × 10-8 ~ 2.0 × 10-5 mol·L-1 and detection limit of 5.0 nmol·L-1 (S/N = 3). The newly prepared carbon paste electrode was successfully applied for As(III) determination in Yangzonghai Lake water with RSD of less than 3.6 % (n = 3) and recovery in the range of 100.7 ~ 115.0 %. DOI: http://dx.doi.org/10.5755/j01.ms.24.4.18499